Corporate Social Responsibility Puspenerbal through Instagram in Building Brand Image: Corporate Social Responsibility Puspenerbal melalui Instagram dalam Membangun Citra Merek - Zhadad, Naufal Rafi; Hariyanto, Didik (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Social media platforms such as Instagram have become strategic tools for organizations to communicate values and activities to a broad audience. Specific Background: In the context of military institutions like the Pusat Penerbangan TNI Angkatan Laut (PUSPENERBAL), Corporate Social Responsibility (CSR) serves not only as a legal obligation but also as a medium to foster public trust and a positive image. Knowledge Gap: While CSR’s role in corporate brand building is widely studied, limited research addresses its integration with Instagram-based communication strategies in military contexts. Aims: This study analyzes PUSPENERBAL’s CSR activities published on Instagram in relation to brand image formation. Results: Using a qualitative descriptive method and the Triple Bottom Line framework (People, Planet, Profit), observations from July–December 2024 reveal that the People aspect includes health, education, and social initiatives; Planet covers wildfire suppression, tree planting, and food cultivation; and Profit is reflected in positive public engagement. CSR posts strengthen brand identity, personality, association, competence, and behavioral perceptions. Novelty: The study offers insights into CSR implementation by a naval aviation unit through a structured digital presence, highlighting non-commercial institutional branding. Implications: Findings suggest that consistent, well-framed CSR content on Instagram can reinforce stakeholder trust and institutional reputation in public sectors. Highlight: CSR strengthens brand dimensions through Instagram content. Triple Bottom Line guides activity focus: People, Planet, Profit. Digital presence fosters stakeholder trust in public institutions. Keywords: Corporate Social Responsibility, Instagram, Brand Image, Triple Bottom Line, Puspenerbal